The school library as seen by its users: the case of the library of Public School Isabel la Católica - M. Ferrer, Linda; Moscoso, Purificación (Revista General de Información y Documentación, 2012)
The purpose of this paper is to evaluate the Library of the School Isabel La Católica through the vision provided by their users, including 5-12 year old students as well as teachers. Their views and perceptions have conducted a subjective evaluation based on the ServQUAL and LibQUAL+ models, that have been adapted to the characteristics of different types of users and to the objectives of the school libraries in the Region of Madrid.